Development and psychometric evaluation of the ethical conflict assessment instrument in nursing: A mixed-method protocol study - Ebrahim Falahati; Mousa Alavi; Mohsen Shahriari (Journal of Education and Health Promotion)
BACKGROUND: Ethical conflict among nurses has a significant impact on their health and the quality of nursing care. The lack of specific ethical and legal signs and obstacles for reporting ethical conflict in nurses has made diagnosis and the management of its negative consequences difficult. This study aims to develop a valid, reliable, evidence-based instrument to assess the ethical conflict of nurses in the sociocultural and managerial context of Iran. MATERIALS AND METHODS: This is an exploratory mixed-method study that will be conducted using a sequential qualitative–quantitative design (QUAL → quan) consisting of four sequential phases to develop the instrument. In the first phase, a qualitative study (semistructured interview) will be conducted to explain nurses’ experiences and perceptions of ethical conflict. In the second phase, a literature review, along with textual content analysis, will be used. In the third phase, the items will be developed and the primary instrument will be designed based on the findings of the qualitative study and the literature review by a panel of experts. Finally, in the fourth phase, the psychometric properties of the Instrument, including validity (face, content, construct, and criterion validities) and reliability (internal consistency and stability) are evaluated. CONCLUSION: The findings of our study will enrich the description of ethical conflict in nursing and will facilitate advancing research in ethical conflict in nursing, a new but important concept in Nursing management. Thus, laying the groundwork for more targeted and effective knowledge-translation interventions in the future.